A-Stage process – Challenges and drawbacks from lab to full scale studies: A review. (1st November 2022) - Guthi, Raja-Sekhar; Tondera, Katharina; Gillot, Sylvie; Buffière, Pierre; Boillot, Mathieu; Chazarenc, Florent
Highlights: This review found a recovery potential between 38 and 48% of influent organics for A-Stage at SRT of 0.3 days. High variability reported in separation efficiency of A-Stage settler. Successful model development of high-rate process to predict A-stage effluent. Abstract: In response to the growing global resource scarcity, wastewater is increasingly seen as a valuable resource to recover and valorise for the benefit of the society rather than another waste that needs treatment before disposal. Conventional wastewater treatment plants (WWTPs) oxidise most of the organic matter present in wastewater, instead of recovering it as a feedstock for biomaterials or to produce energy in the form of biogas. In contrast, an A-Stage is capable of producing a concentrated stream of organic matter ready for valorisation, ideally suited to retrofit existing large plants. This technology is based on the principle of high-rate activated sludge process that favours biosorption and storage over oxidation. In this paper, we summarize peer-reviewed research of both pilot-scale and full-scale studies of A-Stage process under real conditions, highlighting key operational parameters. In the majority of published studies, the sludge retention time (SRT) was identified as a key operational parameter. An optimal SRT of 0.3 days seems to maximize the redirection of influent COD – up to 50% to the sludge flux, while simultaneously keeping mineralization under 25% of total influent COD. Other key optimal parameters are a hydraulic residence time of 30 min and dissolved oxygen levels of 0.5 mg⋅L − 1 . In addition, nutrient removal efficiencies of 15–27% for total nitrogen and 13–38% for total phosphorus are observed. Influence of mixing on settling efficiencies remain largely underexplored, as well as impact of wet weather flow and temperature on overall recovery efficiencies, which hinders to provide recommendations on these aspects. Evolution of modelling efforts of A-Stage process are also critically reviewed. The role of extracellular polymeric substances remain unclear and measures differ greatly according to the different studies and protocols. Better understanding the settling processes by adding Limit of Stokesian and Threshold of Flocculation measures to Sludge Volume Index could help to reach a better understanding of the A-Stage process. Reliable modelling can help new unit processes find their place in the whole treatment chain and help the transition from WWTPs towards Wastewater Resource Recovery Facilities.